Analisis Penerapan Pajak Karbon di Indonesia : Perbandingannya dengan Finlandia, Swedia dan China - Divaka Sukma Krismika; Muhammad Abdul Aris (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study analyzes the implementation of carbon tax in Indonesia and compares it with similar policies in Finland, Sweden, and China. Each country faces distinct challenges that are adapted to their respective social, economic, and environmental contexts. Finland and Sweden have successfully implemented carbon taxes with high rates, using the revenue to fund environmental and social programs, supported by public backing and collaboration between the government and industrial sectors. China, still in the early stages of implementation, has developed an emissions trading system and made large investments in renewable energy. Indonesia, as a country just beginning with Law No. 7 of 2021, faces challenges in implementation mechanisms and lacks public awareness. The research employs a descriptive qualitative approach with literature study as the data collection technique. The study suggests that the Indonesian government should improve socialization and gradually set carbon tax rates while considering the transition to green technologies in the industrial sector.